1992
DOI: 10.1002/chin.199233042
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Temperature‐Dependent Low‐Resolution Microwave Studies of m‐ Iodoanisole, m‐Bromoanisole, m‐Nitroanisole and m‐Anisaldehyde.

Abstract: 1992 microwave spectra microwave spectra (organic substances) K 2550 33 -042 Temperature-Dependent Low-Resolution Microwave Studies of m-Iodoanisole, m-Bromoanisole, m-Nitroanisole and m-Anisaldehyde. --(SORENSON, S. A.; TRUE, N. S.; OTT, C. M.; BOHN, R. K.; FARAG, M. S.; J. Mol. Struct. 268 (1992) 1-3, 123-133; Dep. Chem., Univ. Calif., Davis, CA 95616, USA; EN)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…For example, Wakabayashi et al (4,11) and Strom et al (12) have shown that N-acylation of derivatives based on a sequence of bovine lactoferricin B (amino acids 17-41) resulted in higher * This work was supported in part by EC-specific RTD Programme Grant QLK2-CT-2002-01001, "Antimicrobial Endotoxin Neutralizing Peptides to Combat Infectious Diseases." 1 Supported by German Science Foundation Grant AN301/5-1. 2 Present address: Sanford-Burnham Medical Research Institute, 10901 North Torrey Pines Rd., La Jolla, CA 92037.…”
Section: Lactoferrin (Lf)mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wakabayashi et al (4,11) and Strom et al (12) have shown that N-acylation of derivatives based on a sequence of bovine lactoferricin B (amino acids 17-41) resulted in higher * This work was supported in part by EC-specific RTD Programme Grant QLK2-CT-2002-01001, "Antimicrobial Endotoxin Neutralizing Peptides to Combat Infectious Diseases." 1 Supported by German Science Foundation Grant AN301/5-1. 2 Present address: Sanford-Burnham Medical Research Institute, 10901 North Torrey Pines Rd., La Jolla, CA 92037.…”
Section: Lactoferrin (Lf)mentioning
confidence: 99%
“…5 is an iron-binding glycoprotein found in milk (1) and in exocrine secretions of mammals as well as in granules and neutrophils during inflammatory responses (2,3). The pepsin cleavage fragment lactoferricin, comprising amino acid residues 1-45 of the N terminus of human LF and 17-41 of bovine LF, is one example of naturally occurring antimicrobial peptides (4).…”
Section: Lactoferrin (Lf)mentioning
confidence: 99%